Prospective study of clinical and functional outcome of total knee replacement in osteoarthritic knee - Kadam, Rahul V.; Yadav, Sunil; Chhallani, Abhay; Sharma, Chinmoy (International Journal of Research in Orthopaedics, 2016)
Background: Total knee arthroplasty (TKA) is now a reliable treatment for osteoarthritis. The aim of this study was to study the clinical and functional outcome of total knee arthroplasty using knee society score and to find association between knee functional score and knee clinical score. Methods: We conducted a prospective analysis of 40 cases of osteoarthritis knee patients at a tertiary care centre in Mumbai over a period of two years. Those patients who underwent total knee arthroplasty were assessed clinically and functionally using knee society score. Results: The mean preoperative knee clinical score (KCS) was 49.40±13.79 which was increased to a postoperative score of 86.08±5.64 at the end of 6 month. Similarly the mean preoperative knee functional score (KFS) was 32.75±11.79 which was increased to a postoperative score of 84.43±9.59 at the end of 6 month. There was significant increase in KCS and KFC score during follow up at 1, 3 and 6 month interval. There was significant association between knee functional score and knee clinical score at every interval. Conclusions: Total knee arthroplasty improves the functional ability of the patient and the ability of the patient to get back to pre-disease state, which is to have a pain free mobile joint, as reflected by the improvement in the post-op knee clinical score and knee functional score.